Phenotyping Fasciola hepatica populations for albendazole sensitivity by in vitro egg hatch test - Herschell Kelly, Emily (2025)
The liver fluke Fasciola hepatica is a major cause of morbidity and mortality in ruminant livestock in many parts of the world and infection results in substantial economic losses to the sector. Intensive use of highly effective triclabendazole (>99% efficacy) to control the impact of F. hepatica infection has resulted in widespread resistance. Alternative anthelmintics, like the adulticide albendazole (ABZ) (≥80% efficacy), are often employed to reduce transmission. This study reports in vivo controlled efficacy tests (CET) and in vitro egg hatch test (EHT) evaluation of ABZ sensitivity for two F. hepatica isolates, one from Argentina (Ag) and one from Sweden (E). For each isolate CET: Sheep (n= 6) were infected with ~200 metacercariae, three were treated at 12 weeks post-infection with ABZ (7.5mg/kg), three were left untreated, total worm burden was calculated at necropsy 14 days post-treatment. A ≥80% reduction in CET = ABZ susceptible. EHT: Five x 200 eggs were exposed to ABZ (5, 0.5, 0.05 μM) or MeOH only. Ovicidal activity (%OA) at the discriminating dose (0.5μM) and statistical difference in egg development rate was calculated (pairwise t-test). Isolates were identified as: a) resistant = %OA ≤40%, no statistical difference, b) susceptible = %OA ≥70%, statistically significant difference, c) equivocal = between %OA >40% and <70%. For isolate Ag, CET = 57.65% reduction in worm burden in ABZ+ sheep compared to untreated controls (ABZ- mean = 85 ±21.8 SD, ABZ+ mean = 36 ± 7.94 SD, p = 0.047), indicating ABZ resistance. In EHT at the 0.5μM discriminating dose, % OA = 45.6% ± 1.96 SD and 41.2% ± 1.5 SD development rate (p = 0.01) indicating they fell in the equivocal range. For isolate E CET = 89.23% reduction in worm burden (ABZ- mean = 97.5 ± 6.36 SD, ABZ+ mean = 10.5 ± 9.19 SD, p = 0.012), indicating ABZ susceptibility. In EHT %OA = 74.0% ± 3.5 SD at 0.5 μM, (p < 0.001) and development rate of 19.6% ± 3.5 SD (p< 0.05), indicating ABZ susceptibility. The EHT can reliably screen F. hepatica populations for their susceptibility to ABZ, but it may only detect ABZ resistance in highly resistant populations. However, it is a valuable screening method for phenotyping parasites for molecular studies on signatures of ABZ resistance.